Penentuan Kondisi Optimum Desorpsi Anion Nitrit Dari Adsorben Silika Mesopori Termodifikasi DMA (Dimethylamine) - Deni Marlina; Budhi Oktavia; Sri Benti Etika; Syamsi Aini (Departemen Kimia FMIPA UNP, 2023)
Mesoporous silica is a solid silica having a pore size of 2-50 nm. Mesoporous silica can be immobilized to the surface. Modification of mesoporous silica with dimethylamine aims to modify amine compounds. Mesoporous silica with the addition of amine compounds reacted with GPTMS can be used as nitrite anion adsorption to see the absorption of silica to nitrite anions using the column method, the adsorption capacity of nitrite anions is 0.0182 mg/g with an absorption percentage of 96.71%. Then the desorption process was carried out, the factor used to see the desorption ability was the type of desorption, namely hydrochloric acid (HCl) with the release of 0.0071 mg of nitrite anion from 0.0085 mg of nitrite anion that was absorbed and the percentage of desorption was 83.52% and a concentration factor with the optimum concentration of 0.15M HCl with the release of 0.0091 mg of nitrite anion with 100% desorption percentage.